Comparative analysis of Regional Innovation System in different types of regions: Evidence of Madrid, Basque country and Andalucía - Jandova,Michaela (2014)
Regional innovation system (RIS) is a popular concept between policy makers and researchers. Regional government create RIS policies with the aim to increase competitiveness and gain regional development. Previous research about RIS emphasize the importance of adapting the policy to a certain region based on its specifications, limitations and strengths. The research analyses three Spanish regions, Madrid, representing metropolitan region , Basque country, representing old industrial region and Andalucía, representing peripheral region. The research analysis the similarities and differences between RIS and RIS policies in the regions and linkages between the region specifications and the theoretical framework.
Keywords: metropolitan and old industrial region; Peripheral; Regional Innovation System; Policies; Spain